2022
DOI: 10.1155/2022/5766434
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Role of 4-Octyl Itaconate in Concanavalin A-Induced Autoimmune Hepatitis

Abstract: 4-Octyl itaconate (OI) is a novel anti-inflammatory metabolite that exerts protective effects in many various disease models. However, its function in autoimmune hepatitis- (AIH-) associated hepatic injury has not been investigated. In this study, we successfully used concanavalin A (Con A) to establish an AIH-associated liver injury model. Furthermore, we investigated the effect of OI in Con A-induced liver injury and found that OI mitigated Con A-induced histopathological damage. OI administration reduced se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The primary antibodies are listed in Additional file 1: Table S1. Immunohistochemical analysis of inducible nitric oxide synthase (iNOS), F4/80, high-mobility group box 1 protein (HMGB1), and Nrf2 was performed as previously described (Yang et al 2022). The relative content and positive cells in the islets were determined by ImageJ.…”
Section: Histological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The primary antibodies are listed in Additional file 1: Table S1. Immunohistochemical analysis of inducible nitric oxide synthase (iNOS), F4/80, high-mobility group box 1 protein (HMGB1), and Nrf2 was performed as previously described (Yang et al 2022). The relative content and positive cells in the islets were determined by ImageJ.…”
Section: Histological Analysismentioning
confidence: 99%
“…A derivative diverted from the TCA cycle, itaconate has recently become the focus of the immunometabolism field due to its anti-inflammatory properties that negatively regulate cytokine production and the inflammatory response (Mills et al 2018). In accumulating studies, it was reported that itaconate is important in inflammatory-associated diseases via anti-inflammatory and antioxidant properties, such as acute lung injury (Xin et al 2021;Li et al 2020;Liu et al 2021), autoimmune hepatitis (Yang et al 2022), vitiligo (Xie et al 2022), ischemia-reperfusion injury (Yi et al 2020;Cordes et al 2020), osteoclast-related diseases (Sun et al 2019), cancer (Zhan et al 2022), and renal fibrosis (Tian et al 2020). The functions attributed to itaconate predominantly include aerobic glycolysis inhibition and transcription factor NF-E2-related factor 2 (Nrf2) activation (Mills et al 2018;Liao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of oxidative stress and inflammation, the KEAP1-Nrf2 complex is disassociated, and Nrf2 is translocated to cell nuclei, where it regulates the antioxidant response element (ARE) to drive the expression of ARE-dependent genes and the gene encoding various detoxifying enzymes [ 64 , 65 ]. Studies have demonstrated that DI and 4-OI play effective roles in antioxidation by activating Nrf2 and inactivating NF-κB [ [66] , [67] , [68] , [69] , [70] ]. Because it is an a,β-unsaturated dicarboxylic acid with a mild electrophilic effect, itaconate has been used by scientists to modify the cysteine residue of KEAP1 through Michael addition reaction to inhibit the activity of KEAP1 and prevent Nrf2 degradation.…”
Section: Roles For Itaconate In Regulating the Inflammatory Immune Re...mentioning
confidence: 99%
“…The primary antibodies are listed in Supplementary Table S1. Immunohistochemical analysis of inducible nitric oxide synthase (iNOS), F4/80, high-mobility group box 1 protein (HMGB1), and Nrf2 was performed as previously described (22). The relative content and positive cells in the islets were determined by ImageJ.…”
Section: Histological Analysismentioning
confidence: 99%
“…A derivative diverted from the TCA cycle, itaconate has recently become the focus of the immunometabolism eld due to its anti-in ammatory properties that negatively regulate cytokine production and the in ammatory response (18). In accumulating studies, it was reported that itaconate is important in in ammatory-associated diseases by anti-in ammatory and antioxidant properties, such as acute lung injury (19)(20)(21), autoimmune hepatitis (22), vitiligo (23), ischemia-reperfusion injury (24,25), osteoclast-related diseases (26), cancer (27), and renal brosis (28). The functions credited to itaconate predominantly include aerobic glycolysis inhibition and transcription factor NF-E2-related factor 2 (Nrf2) activation (18,29).…”
Section: Introductionmentioning
confidence: 99%